AS DIMENSÕES DA ORGANIZAÇÃO POSITIVA E SEUS IMPACTOS SOBRE O BEMESTAR DOS TRABALHADORES - Chiuzi, Rafael Marcus (2006)
Organizational characteristics have been studied recently under a different point of view. Today, more emphasis has been given to the positive aspects that make it possible for employees to have positive feelings towards their employer organization and towards the work itself. The current imposed challenges refer to the identification of positive organizational characteristics that allow such growth of the worker. Such characteristics are postulated as beneficial to the organizations, for resulting in greater productivity and profitability, as well as for promoting the well-being of the employees. The objective of this study was to analyze the impacts that the dimensions of the positive organization have over the well-being of the employees. The well-being of the employees was divided into two areas: subjective well-being (composed by general satisfaction with life, positive and negative affects) and well-being at work (composed by three dimensions: job satisfaction, job involvement and affective organizational commitment). Positive organization was conceived as a construct composed by three dimensions: perceived organizational support, perceived organizational justice (distributive and procedural justice) and trust of the employee to the organization. The sample was composed by 200 employees of diverse companies in the State of São Paulo, being 55 of them male, and 145 female, both single and married, with scholar level distributed from complete elementary and middle school up to complete post-graduation. The instrument used to collect data was a self-administered questionnaire composed by nine scales that measured the variables of the study. The results of this research revealed that subjective wellbeing and well-being at work are interrelated. Multiple regression analysis presented that the positive organization dimensions had greater impacts on the well-being at work in relation to the subjective well-being, with special attention to the capability of trust of the employee to the organization when it comes to explaining the well-being of the employees, either in their personal life domains or in their context of work. According to these results, trust of the employee to the organization, perception of organizational justice and perceived organizational support could be pointed out as important dimensions of the positive organization to promote and protect the wellbeing of the employees. Further research should include other positive organizational characteristics to broaden the explanation of the variance of the employee s well-being